2006
DOI: 10.1128/aac.50.1.38-42.2006
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin-Resistant Salmonella enterica Serovar Typhimurium Strains Are Difficult To Select in the Absence of AcrB and TolC

Abstract: It has been proposed that lack of a functional efflux system(s) will lead to a lower frequency of selection of resistance to fluoroquinolones and other antibiotics. We constructed five strains of Salmonella enterica serovar Typhimurium SL1344 that lacked efflux gene components of resistance nodulation cell division pumps (acrB, acrD, acrF, acrBacrF, and tolC) plus three strains that lack genes that effect efflux gene expression (marA, soxS, and ramA) and a hypermutable strain (mutS::aph). Strains were exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
95
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 42 publications
(58 reference statements)
8
95
0
Order By: Relevance
“…This finding may have baring on the observation that drug efflux pump deficiency greatly slows down the evolution of target resistance mutations among pathogens (5,6,8,17). Our analysis suggests, in other words, target resistance masking in combination with growth-bistability to be a previously unrecognized cause of delayed drug resistance development among pathogens under drug efflux pump deficient conditions.…”
mentioning
confidence: 69%
“…This finding may have baring on the observation that drug efflux pump deficiency greatly slows down the evolution of target resistance mutations among pathogens (5,6,8,17). Our analysis suggests, in other words, target resistance masking in combination with growth-bistability to be a previously unrecognized cause of delayed drug resistance development among pathogens under drug efflux pump deficient conditions.…”
mentioning
confidence: 69%
“…Deletion of acrD or acrF from S. enterica serovar Typhimurium had little effect on the MICs of clinically relevant antibiotics (40). However, it was shown that when either of these genes was deleted, AcrB expression was increased (40); likewise, when acrB was deleted, expression of acrD or acrF increased (40,185). It may be that the bacterium can compensate for the lack of AcrD or AcrF, and consequently there is no effect on MICs.…”
Section: Efflux Pumps Of Clinically Relevant Bacteria That Confer Mdrmentioning
confidence: 95%
“…1). Mutants of S. enterica serovar Typhimurium that lack various efflux pump genes have been constructed (15,25,40,185). Mutants lacking AcrB were hypersusceptible to quinolones, tetracycline, chloramphenicol, bile salts, SDS, Triton-X100, acriflavine, ethidium bromide, cetyltrimethylammonium bromide (CTAB), and triclosan.…”
Section: Efflux Pumps Of Clinically Relevant Bacteria That Confer Mdrmentioning
confidence: 99%
“…Ciprofloxacin-resistant mutants (104-cip and 5408-cip) were selected from serovar Enteritidis strains 104 and 5408. Salmonella enterica serovar Typhimurium knockout strains L110 acrB::aph, L130 marA::aph, L133 ramA::aph, and L135 soxS::aph derived from SL1344 (12,41) and donor E. coli strains carrying the plasmids pBP513 gyrA ϩ , pBP548 gyrB ϩ , and pBP568 parE ϩ were also used and kindly provided to L. Piddock by P. Heisig (15).…”
Section: Methodsmentioning
confidence: 99%